Mites (Arachnida, Acari) on Citrus sinensis L. Osbeck orange trees in the state of Amazonas, Northern Brazil - Bobot,Teiamar da Encarnação (2011)
Despite the importance of citriculture in Brazil, very little is known about mite populations in citrus crops in the Northern Region. In the municipality of Manaus, 12 sprayed sweet orange orchards were surveyed every two weeks during seven months to record mite species amount, and to describe the abundance and distribution of the most important species. The size and age of the orchards varied from 3,360 to 88,080 m² and seven to 25 years, respectively. In the fourteen sampling period, leaves, twigs and fruits were collected from 12 trees, one per orchard. In total, 3,360 leaves, 672 twigs and 1,344 fruits were sampled from 168 trees. Mites were manually extracted from the fruits, and by the washing method on leaves and twigs. We identified pests with the potential to cause economic loss. Fourteen species of phytophagous and mycophagous mites from Eriophyidae, Tarsonemidae, Tenuipalpidae, and Tetranychidae were recorded. Brevipalpus phoenicis (Geijskes 1939) and Phyllocoptruta oleivora (Ashm., 1879), the two commonest phytophagous mites in other Brazilian regions were dominant, showing that local orchards are susceptible to their infestation. Eleven predatory mites were recorded, comprising 10% of the mite population, belonging to Phytoseiidae and Ascidae. Phytoseiidae was the richest family, with ten species. The results are discussed in relation to the temporal variation aspects and habitat use of the most important species. Long-term research encompassing chemical applications followed by evaluations of the mite community are necessary for a better management of the orchards, taking into consideration the seasonal phenology of key pests.